Effects of Mixed Saline and Fresh Water Sprinkler Irrigation on the Rhizosphere Soil Microbial Community of Summer Maize - Tieqiang Wang; Zikang Guo; Hanbo Wang; Weidong Li; Wenxu Sheng; Shuantang Zhang; Dasheng Zhang (Agriculture)
Mixing saline and fresh water can help to increase the agricultural water utilization rate and solve the water shortage situation, but its role on rhizosphere microbes is unknown. This study revealed the effects of mixed saline and freshwater sprinkler irrigation at different proportions on the rhizosphere soil microbial community of summer maize. Compared to freshwater sprinkler irrigation, sprinkler irrigation with 2 g·L−1 of mixed saline and fresh water significantly increased the bacterial α-diversity and significantly affected the structure and composition of bacterial communities, increasing the number of OTUs, the ACE index, and the Shannon index in the rhizosphere soils, whereas sprinkler irrigation with 3 g·L−1 did not lead to significant changes. In addition, there was a significant difference in β-diversity between the mixed saline and freshwater sprinkler irrigation and the freshwater sprinkler irrigation. Principal coordinate analysis revealed that the 2 g·L−1 and 3 g·L−1 sprinkler irrigation treatments were closer to each other, but both were at a greater distance from the freshwater sprinkler irrigation, indicating that mixed saline and freshwater irrigation significantly affected the structure of rhizosphere soil bacterial communities. Ammonium nitrogen, alkaline dissolved nitrogen, and total nitrogen all affected the soil bacterial community structure by more than 10%, with ammonium nitrogen being the most influential environmental factor. The relative abundance of most microbes in the mixed saline and freshwater sprinkler treatments was positively correlated with ammonium nitrogen, especially in the 2 g·L−1 treatment, while that of most microbes in the freshwater sprinkler treatment was negatively correlated with ammonium nitrogen. In conclusion, selecting a sprinkler irrigation model with a mineralization level of mixed saline and freshwater not exceeding 2 g·L−1 could enhance the rhizosphere soil microbial community while conserving water resources.